2022
DOI: 10.3390/life12050723
|View full text |Cite
|
Sign up to set email alerts
|

Any Future for Faecal Microbiota Transplantation as a Novel Strategy for Gut Microbiota Modulation in Human and Veterinary Medicine?

Abstract: Alterations in the composition of the intestinal microbiome, also known as dysbiosis, are the result of many factors such as diet, antibiotics, stress, diseases, etc. There are currently several ways to modulate intestinal microbiome such as dietary modulation, the use of antimicrobials, prebiotics, probiotics, postbiotics, and synbiotics. Faecal microbiota transplantation (FMT) represents one new method of gut microbiota modulation in humans with the aim of reconstructing the intestinal microbiome of the reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 216 publications
(341 reference statements)
1
8
0
Order By: Relevance
“…Recently, research on the modulation of the gut microbiota has focused on fecal microbiota transplantation (FMT), which refers to a method of transfer of feces from a healthy individual to the gut of a diseased recipient via an enema, endoscopy, nasogastric tube, or by indigestion peroral capsules ( Takáčová et al, 2022 ). It is considered an innovative, effective, and safe technique to treat challenging diseases like Clostridium difficile ( Bárcena et al, 2019 ), Campylobacter jejuni ( Brooks et al, 2017 ; Heimesaat et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research on the modulation of the gut microbiota has focused on fecal microbiota transplantation (FMT), which refers to a method of transfer of feces from a healthy individual to the gut of a diseased recipient via an enema, endoscopy, nasogastric tube, or by indigestion peroral capsules ( Takáčová et al, 2022 ). It is considered an innovative, effective, and safe technique to treat challenging diseases like Clostridium difficile ( Bárcena et al, 2019 ), Campylobacter jejuni ( Brooks et al, 2017 ; Heimesaat et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Personalized and targeted modulation of gut microbiota has all the prerequisites to become a key strategy for the prevention and supportive therapy of chronic diseases. [44,45]. Personalized and precision medicine creates prerequisites for the application of new methods of treatment for many chronic diseases aimed at modifying the gut microbiome, including cancer therapy.…”
Section: Personalized and Targeted Microbiota Modulation And Its Pote...mentioning
confidence: 99%
“…Postbiotics refer to dead microorganisms or microbial metabolic products beneficial to gut health [ 91 ]. Although postbiotics do not include live microorganisms, they may have beneficial properties based on their pleiotropic effects, including anti-inflammatory, antioxidant, immunomodulatory and anticancer properties [ 92 , 93 ]. After an exhaustive review of the literature, we found no study investigating the use of a product with only postbiotic properties in dogs with CIEs.…”
Section: Limitations and Reconsideration Of The Current Classificationmentioning
confidence: 99%